AB0547 Lymphadenopathy in systemic lupus erythematosus: clinical relevance and histological subtypes. (12th June 2018) - Berbel, A.; Estevez, M.; Freire, M.; González, E.; González-Vázquez, L.; Carballo, I.; Sopeña, B.; ,
Abstract : Background: Some patients with Systemic Lupus Erythematosus (SLE) have lymphadenopathy (LAP) at diagnosis or at follow-up. The prevalence of LAP in SLE was 59% in the oldest series, 1 12% in the 1993 EUROLUPUS series 2 and in the last two decades its prevalence was not mentioned. However, the presence of LAP and their histological type may have clinical relevance. 3 Objectives: To study the prevalence and histologic charasteristics of LAP in a cohort of patients with definite SLE and evaluate its relationship with clinical manifestations. Methods: All patients diagnosed with SLE according to the 1997-ACR criteria at the Autoimmunity Units of three different hospitals since 2005 were followed looking for lymph node enlargement at every consult. The moment when LAP was detected, the concomitant clinical symptoms, SLE manifestations and laboratory variables were recorded. The group of patients with and without LAP were compared. A tissue sample was obtained when indicated. All patients agree to participate in the study. Results: 103 patients with definite SLE were included in the study. Valuable LAP (>10 mm) was found in 28 patients (27%). The gender and age of SLE patients with and without LAP was similar (80% vs 78% females, and 34±15 vs. 40±28 years respectively). LAP was detected at the time of SLE diagnosis in 54% of patients. Fever was significantly more frequent in patients with LAP (60% vs 5%, p<0.01) like dermopathy (86% vs. 60%; p<0.05) and serositis (45% vs 16% p<0.01). High titters of anti-dsDNA antibodies (71% vs. 42%; p<0.05) and hypocomplemetemia (89% vs. 60%; p<0.05) were also more frequent in patients with LAP. A total of 28 tissue samples were obtained in 17 patients (FNA 6, Ultrasound-guided biopsy 6 and surgical excision in 17). The histopathological study showed: Reactive lymphadenitis 20, histiocytic necrotizing lymphadenitis in 6 and Non-Hodgkin Lymphoma in 2 (B-cell lymphoma on methotrexate treatment, and a Burkitt lymphoma). All 6 patients with SLE and histiocytic necrotizing lymphadenitis have cutaneous involvement but none of them developed lupus nephritis. Conclusions: Patients con SLE and lymphadenopathy had significantly more fever, cutaneous lesions and serositis. High levels of anti-dsDNA antibodies and hypocomplementemia were more frequent in these patients. In some occasions malignancy could be the cause of lymphadenopathy. References: [1] Dubois EL, Tuffanelli DL. Clinical Manifestations of Systemic Lupus Erythematosus. Computer Analysis of 520 Cases. JAMA1964; 190:112–19 [2] Cervera R. Khamashta M, Font J, et al. Systemic Lupus Erytematosus: Clinical and Immunologic Patterns of Disease Expression in a Cohort of 1, 000 Patients. Medicine1993; 72(2):113–24 [3] Shapira Y, Weinberger A, Wysenbeek AJ. Lymphadenopathy in Systemic Lupus Eritematosus. Prevalence and Relation to Disease Manifestations. Clin Rheumatol1996; 15(4):335–38 Disclosure of Interest: None declared